Tuberculous osteomyelitis of the mandible impersonating dentoalveolar abscess: a case report - Popli Harsha; Gupta Ambika; Lonyal Jatin; Singh Aarti (EDP Sciences, 2022)
Introduction: Tuberculosis (TB) affects 8 million new people every year, with developing countries under its strong clout. Although tuberculosis can affect any part of the body involving both soft and hard tissues; such an occurrence in the maxillofacial bones in the form of tuberculous osteomyelitis is relatively rare. Due to the rarity of the lesion and lack of sufficient documentation, its incidence can be expected to be more than what has been reported so far. Observation: So, here is a case of a 21-year-old male who presented with pain and swelling on the mandible, diagnosed as tuberculous osteomyelitis after an initial diagnosis of dentoalveolar abscess. Conclusion: As dentists and as oral medicine practitioners, it is of utmost importance for us to be aware about uncommon diseases affecting the jaws such as tuberculous osteomyelitis, which tend to mimic dental infections in some cases to prevent misdiagnosis and provide holistic care to the patient.